Tax evasion among civil servants in Malaysia / Sarah Hannani Abdul Rahim and Nur Alia Sama’on - Abdul Rahim, Sarah Hannani; Sama’on, Nur Alia (2022)
OECD defines tax evasion as illegal arrangements where liability to tax is hidden or ignored, like the taxpayer pays less tax than he is legally obligated to pay by hiding income or information from the tax authorities.There had been many studies conducted on tax evasion and its relationship with the determinants from Theory of Planned Behaviour. This study paper aims to investigate whether the variables from Theory of Planned Behaviour, namely attitude, subjective norms and perceived behavioural control have significant influence towards tax evasion behaviour. The sample that will be used in this study is civil servants in Malaysia. The study utilized survey questionnaires as its data collection method. The findings show there is a significant influence between perceived behavioral control and tax evasion behaviour. However, there is no significant relationship between attitude and subjective norms with tax evasion. In summary, perceived behavioral control was detected as a significant determinant for tax evasion behaviour depending on the opportunities and obstacles that the taxpayers faced while paying the tax.